Essays on commodities and international macroeconomic interactions - Kim, M (2018)
This thesis introduces commodities into otherwise standard closed economy or open economy macro models. Chapter 1 sheds light on the fact that as trading in commodity derivatives tied to commodity prices has increased massively since the 2000s, they have begun to act as an asset class in recent years. It shows that financial intermediaries’ investments in commodities play an important role in the recent reduction in the impacts of commodity price shocks on the economy. Chapter 2 adds commodities and different commodity trade structures of countries to a standard two-country model. It shows that U.S. business cycle comovements with commodityexporting countries are stronger than those with commodity-importing countries and that the model produces better international business cycle statistics between the U.S. and commodityexporting countries compared to the standard model. These results imply that the two elements should be considered to properly analyse international macroeconomic interactions between the U.S. and commodity-exporting countries. Chapter 3 studies international transmission of U.S. monetary policy shocks to commodity-exporting and commodity-importing countries. The chapter first empirically shows that the shocks have stronger effects on commodity-exporting countries than commodity-importing countries, and then augments a standard three-country model to include commodities and different commodity trade structures of countries. Consistently with the empirical evidence, in the model an expansionary monetary policy shock to the U.S. increases aggregate output of commodity-exporting countries by more than that of commodity-importing countries. This is because the increased U.S. aggregate demand triggered by the shock leads to rises in its demand for commodities and real commodity prices, and thus exports of commodity-exporting countries go up by more than those of commodity-importing countries.